2021
DOI: 10.1108/jed-09-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the impact of financial intermediation on economic growth: evidence from Turkey

Abstract: PurposeThis study seeks to investigate the impact of financial intermediation on economic growth in Turkey using annual data spanning 1970–2017.Design/methodology/approachBased on the results of the augmented Dickey–Fuller and Phillips–Perron unit root tests for stationarity, the authors employ the Autoregressive Distributed Lag (ARDL) bounds testing to cointegration to establish the long-run impact of financial intermediation alongside other control factors on economic growth. The study also examines the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Moreover, Table 2 also represents the pairwise Pearson correlations between employed variables. The correlation between the independent variables is less than 80% proves that the issue of multicollinearity is not undermining our findings ( Yakubu et al., 2021 ).…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Moreover, Table 2 also represents the pairwise Pearson correlations between employed variables. The correlation between the independent variables is less than 80% proves that the issue of multicollinearity is not undermining our findings ( Yakubu et al., 2021 ).…”
Section: Resultssupporting
confidence: 50%
“…The index ranges from 0 to 1, where a higher value indicates more financial openness ( Hussain et al., 2021 ; Rahman et al., 2021 ; Romer and Romer, 2010 ) Political Stability PSI The political stability index reflects the possibility of politically-motivated violence, including terrorism. Variable ranges from −2.5 to 2.5, with higher values indicating more political stability ( Rahman et al., 2021 ; Yakubu et al., 2021 ) Source: Developed by the authors. …”
Section: Methodsmentioning
confidence: 99%
“…Prior to the ARDL estimation, we assess the level of integration of the variables by using the Phillips–Perron (PP) unit root test which is consistent with the studies by Amaefula (2021), Firat (2016), Yakubu, Abokor, and Gedik Balay (2021). To apply the ARDL technique, the variables are required to be integrated at level (I(0)) or first difference (I(1)).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there should be no serial correlation or heteroscedasticity, meaning that the residuals of the model should not be correlated with each other and the variance of the residuals should be constant across all observations. Prior to the ARDL estimation, we assess the level of integration of the variables by using the Phillips-Perron (PP) unit root test which is consistent with the studies by Amaefula (2021), Firat (2016), Yakubu, Abokor, and Gedik Balay (2021). To apply the ARDL technique, the variables are required to be integrated at level (I(0)) or first difference (I(1)).…”
Section: Analytical Approachmentioning
confidence: 99%
“…Using the ARDL model with data extending from 1978 to 2015, Tursoy and Faisal (2018) demonstrated that deposit growth (a measure of financial depth) influences economic growth in Cyprus. Using annual data from 1970 to 2017, Yakubu et al (2021) examined the effect of financial intermediation on economic growth in Turkey. To determine the long-run and short-run relationship between the variables, the authors applied the ARDL bounds testing to cointegration.…”
Section: The Empirical Literaturementioning
confidence: 99%